ANALISIS TRANSPOSISI DAN MODULASI PADA BUKU TEORI BUDAYA TERJEMAHAN DARI BUKU CULTURE THEORY (Lingua, 2011)
This descriptive-qualitative research aims at describing transposition and modulation in the book entitled TeoriBudaya and describing the accuracy, acceptability, and readability of the translated sentences containingtransposition and modulation. The data of this research are English sentences in Culture Theory translated intothe book entitled Teori Budaya using transposition and modulation. The information is also provided onaccuracy, acceptability, and readability given by the raters. The first data were taken from Culture Theory andTeori Budaya using observation and note-taking techniques. And the second data were collected from aquestionnaire and in-depth interviews. The results of the research show that the techniques of transposition andmodulation have advantages as well as disadvantages. In term of accuracy, transposition is more accurate thanmodulation but modulation has a higher level of acceptability and readability than transposition has. Related tothe accuracy, acceptability, and readability, from 100 data of transposition under study, there are 86%categorized as accurate, 73% as acceptable, and 91% as easy. On the other hand, from 80 data of modulationanalyzed, there are 83.75% categorized as accurate, 73.75% as acceptable, and 93.75% as easy. From thisanalysis, the translator needs to have good competence in translating and the translated book is of good quality.The translator should be able to set himself free from the influence of the sentence structure of the sourcelanguage and to express messages in idomatic bahasa Indonesia.Kata Kunci: Transposisi, modulasi, keakuratan, keberterimaan, keterbacaan